LncRNA UCA1 Induces Acquired Resistance to Gefitinib by Epigenetically Silencing CDKN1A Expression in Non-small-Cell Lung Cancer - Xu, Tianwei; Yan, Shuai; Wang, Mengwei; Jiang, Lihua; Ma, Pei; Lu, Binbin; Chen, Qinnan; Wei, Chenchen; Wang, Zhaoxia (Frontiers in Oncology, 2020)
Lung cancer is the most common cancer globally and is associated with high morbidity and mortality. Gefitinib has been widely used for treating advanced non-small-cell lung cancer (NSCLC). However, acquired resistance usually develops, although we still know little about the mechanism underlying this. In the present study, we found that the lncRNA UCA1 was upregulated in NSCLC tissues and cells with acquired gefitinib resistance, indicating the special role of UCA1 in gefitinib resistance. Knockdown of UCA1 promoted the sensitivity to gefitinib both in vitro and in vivo by suppressing cell proliferation and inducing apoptosis. Moreover, UCA1 could interact with EZH2 (enhancer of zeste homolog 2) to epigenetically reduce the expression of CDKN1A. Taking the obtained findings together, our study suggests that UCA1 is important for NSCLC to develop gefitinib resistance, and is a potential biomarker for gefitinib resistance and a therapeutic target for advanced NSCLC.